Optimalisasi Pentingnya Konsep Good Governance dalam Sektor Publik dan Privat - Farisna Marhadila; Fiki Putra Firdaus; Ismi Dewi Rahma Kadilla; Putri Fatma Apriliani; Novi Khoiriawati (CV. ITTC INDONESIA, 2024)
Good governance is a concept related to cooperation between government and society to influence policies related to people's lives in politics, economics, social and culture in order to achieve good and democratic government. Public services are the realm of governance elements that carry out very intensive interactions. The aim of this research is to optimize the concept of Good Governance in public services in East Java. This research uses a qualitative, descriptive analytical approach, by analyzing the factors that influence the optimization of the importance of the concept of good governance, especially in the public and private sectors. With a phenomenological approach, secondary data is used in the form of various regulations related to government governance and other literature. Based on research results, the governance index for East Java Province in 2012 was quite good when compared with other provinces in Indonesia and was above the national average, with a score of 6.43, ranking second after Yogyakarta Special Region Province with a score of 6.80. However, in the arena of government, it is the smallest contributor, especially to the principles of justice. It is important to follow up, especially in the principles of justice, both in budget allocations and program policies.